OPTIMALISASI INSTAGRAM ADS UNTUK MENINGKATKAN PROMOSI UMKM MELALUI KONTEN KREATIF - Dewo Adji Suryo Kusumo; Muchammad Ridho Alfarizy; Ananda Tri Bagus Herwanto; M. Alfian Ramadhani (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
Social media has undergone significant development since its introduction in the early 2000s. Today, social media has become an integral part of many people's daily lives, one of which is Instagram. Instagram is a social media platform founded in 2010 by Kevin Systrom. The platform continues to grow and has become one of the most popular social networks in the world. Instagram provides photo and video sharing services, which are highly relevant for digital promotion purposes, especially for Micro, Small, and Medium Enterprises (MSMEs). With the increasing number of users, in 2017 Instagram released a paid advertising feature called Instagram Ads, which helps businesses promote their products more effectively. This study uses a qualitative descriptive method with a case study approach on the Semangkuk Kenyang MSME. The data sources consist of primary and secondary data. Primary data was obtained through direct observation during the digital marketing process. Meanwhile, secondary data was obtained from relevant supporting documents and literature. The results of the study show that the use of Instagram Ads accompanied by creative, innovative, and high-quality visual content can enhance MSME promotion. The consistency of the content theme, balanced with high-resolution images and videos, successfully attracted consumers' attention. Based on Instagram insights data, there was an increase in profile visitors of more than 50% compared to before. This indicates that creative content strategies and the use of Instagram Ads have proven effective in increasing the visibility and success opportunities of Semangkuk Kenyang MSMEs in the digital era.